An assessment of driving seating comfort based on natural fiber material by using digital human modelling and pressure mapping technique - Nur Syazwani, Mohd Noor (2019)
Seating comfort is one of the important indicators while driving especially for a prolong drive. Seat comfort is crucial factor among the competitors of car seat manufacturers. One key factor in producing a comfortable car seat is the material of car seat cushion. A commonly used material in the automotive industry is flexible polyurethane (PU) foam. Currently, the development of renewable products to reduce the usage of petroleum based product has become an essential issue, especially to the environment. This study aims to investigate seating comfort during driving based on hybrid natural fiber by using digital human modelling and pressure mapping technique. The current study attempted to study PU foam filled with natural filler to investigate the mechanical properties of the composite. The PU was mixed with polyol and isocyanate with a ratio of 1:0.6. Three natural fibers were chosen to mix with the PU, which are empty fruit bunched (EFB), kenaf and coir were mixed with different proportions (5wt%, 10wt%, 15wt% and 20wt%) before tested for their mechanical properties . Based on the result obtained, PU reinforced with EFB (5wt%) had good properties, and it was more economical as compared to the other two fillers. A mock-up car seat model was fabricated from the chosen composite which mimicked the size and design of an existing commercial car seat for small cars. Pressure mapping experiment was conducted on both seats to study the pressure distributions of human and seat interaction. A total of 20 healthy subjects with driving experience were randomly selected among Universiti Malaysia Pahang (UMP) students to do the driving session for the pressure distribution experiment. Subjects were required to drive along UMP Pekan route for about 20 minutes before they answered a questionnaire on comfort for both seats. Six main body parts were investigated for pressure distributions which are right buttock, left buttock, right thigh, left thigh, upper back and lower back. Among these six body parts, the average pressure distribution was higher at buttock area (ischial tuberosities), and the least was at the upper back of the body. Heavier subjects had higher average pressure by 22% compared to the lighter subjects, and the area of the pressure was wider. The average pressure of all subjects increased as the time of driving increased. This shows that if the period of driving is longer, the driver might feel discomfort as the pressure increases, which can cause muscle discomfort to the driver. Both car seats had almost same comfort level regarding to the evaluation and pressure mapping study. Hence, hybrid composition material can be used as an alternative material to develop car seat.